2014
DOI: 10.1155/2014/453039
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias Repair: A Single Centre Experience

Abstract: Objectives. To determine the demographics and analyze the management and factors influencing the postoperative complications of hypospadias repair. Settings. Hayatabad Medical Complex Peshawar, Pakistan, from January 2007 to December 2011. Material and Methods. All male patients presenting with hypospadias irrespective of their ages were included in the study. The data were acquired from the hospital's database and analyzed with Statistical Package for Social Sciences (SPSS). Results. A total of 428 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 23 publications
9
36
1
6
Order By: Relevance
“…In this study we took into account fistula, meatal stenosis, and penile skin necrosis as the possible TIP Snodgrass complications, however glans dehiscence, neourethral strictures, diverticula and edema could be considered as complications. 5,7 Moreover, the six month period was considered for the follow-up of fistula, meatal stenosis, and penile skin necrosis complications. In agreement with the current follow-up period of the study, Snodgrass, Villanueva 7 determined in prospective analysis of the available database on follow-up period following primary distal and proximal TIP and TIP reoperations that 64% of urethral complications could be uncovered at the first visit postoperatively and 81% were detectable within the first year following hypospadias repair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we took into account fistula, meatal stenosis, and penile skin necrosis as the possible TIP Snodgrass complications, however glans dehiscence, neourethral strictures, diverticula and edema could be considered as complications. 5,7 Moreover, the six month period was considered for the follow-up of fistula, meatal stenosis, and penile skin necrosis complications. In agreement with the current follow-up period of the study, Snodgrass, Villanueva 7 determined in prospective analysis of the available database on follow-up period following primary distal and proximal TIP and TIP reoperations that 64% of urethral complications could be uncovered at the first visit postoperatively and 81% were detectable within the first year following hypospadias repair.…”
Section: Resultsmentioning
confidence: 99%
“…1 Numerous clinical techniques have been well established in order to repair all defects of hypospadias till now, however there is no single and universal technique. [2][3][4] Hypospadias has been considered the most common abnormal condition of the genital tract in males 3,5 with an annual incidence between 0.8 and 8.2/1000 live male newborns. Normally, the repair of hypospadias is performed following one year of age, and it is suggested that circumcision is better not to be done for the child until the hypospadias repair is accomplished.…”
mentioning
confidence: 99%
“…Uzair and colleagues reported a 9.6% fistula rate with the use of interrupted 6/0 polyglactin 910 suture for urethral closure 15 . There is, however, a long learning curve and as highlighted in a major study by Khan and colleagues that the results tend to improve with time and experience 16 . They reported fistula rates of 38.8%, however, they have included all forms of hypospadias and specialists as well as residents had performed the operations.…”
Section: Discussionmentioning
confidence: 99%
“…They then are reviewed at 3 months, and from then on yearly till 5-6 years of age before discharge. Khan et al [13] reported an increase in complications as a result of lack of magnification and microsurgical instruments. Hypospadias surgery has as steep learning curve, and it is more likely that more complications will be encountered earlier on in practice.…”
Section: Discussionmentioning
confidence: 99%